Nitric Oxide Mitigates Salt Stress by Regulating Levels of Osmolytes and Antioxidant Enzymes in Chickpea - Ahmad, Parvaiz; Abdel Latef, Arafat A.; Hashem, Abeer; Abd_Allah, Elsayed F.; Gucel, Salih; Tran, Lam-Son P. (Frontiers in Plant Science, 2016)
This work was designed to evaluate whether external application of nitric oxide (NO) in the form of its donor S-nitroso-N-acetylpenicillamine (SNAP) could mitigate the deleterious effects of NaCl stress on chickpea (Cicer arietinum L.) plants. SNAP (50 μM) was applied to chickpea plants grown under non-saline and saline conditions (50 and 100 mM NaCl). Salt stress negatively affected growth and biomass yield, leaf relative water content (LRWC) and chlorophyll content of chickpea plants. High salinity increased electrolyte leakage, carotenoid content and the levels of osmolytes (proline, glycine betaine, soluble proteins and soluble sugars), hydrogen peroxide (H2O2) and malondialdehyde (MDA), as well as the activities of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), and glutathione reductase (GR) in chickpea plants. Expression of the representative SOD, CAT and APX genes examined was also up-regulated in chickpea plants by salt stress. On the other hand, exogenous application of NO to salinized plants enhanced the growth parameters, LRWC, photosynthetic pigment production and levels of osmolytes, as well as the activities of examined antioxidant enzymes which is correlated with up-regulation of the examined SOD, CAT and APX genes, in comparison with plants treated with NaCl only. Furthermore, electrolyte leakage, H2O2 and MDA contents showed decline in salt-stressed plants supplemented with NO as compared with those in NaCl-treated plants alone. Thus, the exogenous application of NO protected chickpea plants against salt-induced oxidative damage by enhancing the biosynthesis of antioxidant enzymes, thereby improving plant growth under saline stress. Taken together, our results demonstrate that NO has capability to mitigate the adverse effects of high salinity on chickpea plants by improving LRWC, photosynthetic pigment biosyntheses, osmolyte accumulation and antioxidative defense system.